Biocontrol of Pythium aphanidermatum causing soft rot in ginger with biosurfactant produced by a rhizospheric Bacillus species: Biocontrol of Pythium aphanidermatum with biosurfactant - Goswami, D; Syiem, M B (Journal of Spices and Aromatic Crops, 2021)
Plant growth-promoting rhizobacteria benefit plants by producing phytohormones and acquiring vital nutrients from soil. They also form a shield against potential phytopathogens with the production of antimicrobial compounds such as bacteriocin, biosurfactants etc. In the present study, among various rhizobacteria isolated from ginger rhizosphere, the isolate identified as Bacillus altitudinis VS7 that showed a potent biosurfactant producing ability in the preliminary tests was selected for the further study. Compositional analyses indicated that the biosurfactant produced by VS7 was a surfactin like compound, a cyclic lipopeptide. In both microtitre plate and mycelium growth inhibition studies, the biosurfactant showed dose dependent antagonistic activities against Pythium aphanidermatum that causes soft rot in ginger. Although there are reports of biocontrol activity of various rhizobacteria against soft rot in ginger, this is the firstinformation regarding biocontrol activity of a biosurfactant produced by the rhizobacterium B. altitudinis VS7 against P. aphanidermatum.